Synthesis, characterization and evaluation of antimicrobial efficacy and brine shrimp lethality assay of Alstonia scholaris stem bark extract mediated ZnONPs - Nookala Supraja; T.N.V.K.V. Prasad; Arumugam Dhanesh Gandhi; Devipriya Anbumani; P. Kavitha; Ranganathan Babujanarthanam (Biochemistry and Biophysics Reports, 2018)
Alstonia scholaris is one of the most important medicinal plants and herein, we present the synthesis of zinc oxide nanoparticles using the bark extract of Alstonia scholaris, and evaluation of their antimicrobial efficacy. Stable ZnO nanoparticles were formed by treating 90 mL of 1 mM zinc nitrate aqueous solution with 10 mL of 10% bark extract. The formation of Alstonia scholaris bark extract mediated zinc oxide nanoparticles was confirmed by UV–visible spectroscopic analysis and recorded the localized surface plasmon resonance (LSPR) at 430 nm. Fourier transform infrared spectroscopic (FT-IR) analysis revealed that primary and secondary amine groups in combination with the proteins present in the bark extract is responsible for the reduction and stabilization of the ZnONPs. The crystalline phase of the nanocrystals was determined by XRD analysis and morphology was studied using transmission electron microscopy (TEM). The hydrodynamic diameter (26.2 nm) and a positive zeta potential (43.0 mV) were measured using the dynamic light scattering technique. The antimicrobial activity of Alstonia scholaris ZnONPs was evaluated (in-vitro) using disc diffusion method against fungi, Gram-negative and Gram-positive bacteria which were isolated from the biofilm formed in drinking water PVC pipelines. The results obtained suggested that ZnO nanoparticles exhibit a good anti-fungal activity than bactericidal effect towards all pathogens tested in in-vitro disc diffusion method (170 ppm, 100 ppm and 50 ppm). Further, the toxicity of biosynthesized ZnONPs was tested against Alstonia scholaris to evaluate the cytotoxic effect that displayed LC50 value of 95% confidence intervals.